Effect of Trichoderma sp Application and Giving Goat Manure on Growth and Production of Shallots (Allium cepa L.) - Al Machfudz WDP; Muhammad Nurmansyah (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to determine the effect of the application of Trichoderma sp and the provision of goat manure on the growth and production of shallots (Allium cepa L), carried out in Jiken village, Tulangan District, Sidoarjo Regency, from January to March 2020. The experiment was arranged factorial using a randomized block design. with 2 factors. Factor 1: frequency of application of Trichoderma sp, control, once / 1 week, once / 2 weeks. Factor 2: goat manure dose, control, 5 tonnes / ha, 10 tonnes / ha. From these two factors, 9 treatment combinations were obtained and were repeated 3 times so that there were 27 experimental units. The results showed that the combination of the frequency of Trichoderma sp application and the dose of goat manure did not interact with all the observation variables, both the vegetative phase and the generative phase, while the treatment frequency of Trichoderma sp application had a significant effect on the observed variable plant length at 30 days of age. The number of leaves at the age of 20 days and 30 days of age, the wet weight of the tubers per plant, the dry weight of the tubers per plant showed a very significant effect, with the frequency of application of Trichoderma sp. which is significant in the variable plant length observations at 30 days and 40 days of age, tuber wet weight per plot. With a goat manure dose of 10 tons / ha.